Health and its concepts in the 21st century - Soriano, Joan B.; Lumbreras, Sara (Razón y fe, 2023)
The concept of health is much more difficult to define than the concept of disease. This work summarizes the historical trajectory of the concept of health from the Aztec and Egyptian civilizations to the definition of the World Health Organization in 1948: “A state of complete physical, mental and social well-being, and not merely the absence of disease or infirmity”. More recently, the WHO definition of health has been modified and supplemented with the fourth dimension: spiritual health. It implies a sense of fullness and satisfaction with one’s own life, value system, self-confidence and self-esteem, self-awareness and presence, peace and tranquility with dynamic emotional balance, both internally and towards the environment, morality and truthfulness, selflessness, positive emotions, compassion and willingness to help and support others, responsibility and contribution to the common good and successful handling of the problems and demands of everyday life, as well as social stress. In short, ‘health’ is an evolving and changing concept, which is also very personal. It depends on the age of the individual, their conditions, and their environment, and also on the initial state of each person, among other variables. Transhumanism and its innovations applied to health can revolutionize all these concepts.
Keywords: DALYs; awareness; illness; health; life’s sense